Government House - (:unkn) unknown (Wilsons Ltd., Trinidad, 2009)
A picture of the walkway which leads to the Government House main building. It is lined with tropical plants of the Botanical Gardens and has a fountain at the centre.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Fountains--Trinidad and Tobago; Architecture--Trinidad and Tobago; Gardens--Trinidad and Tobago; President's House, The